2007
DOI: 10.1073/pnas.0608991104
|View full text |Cite
|
Sign up to set email alerts
|

Homer 1a uncouples metabotropic glutamate receptor 5 from postsynaptic effectors

Abstract: Metabotropic glutamate receptors (mGluRs) and Homer proteins play critical roles in neuronal functions including plasticity, nociception, epilepsy, and drug addiction. Furthermore, Homer proteins regulate mGluR1/5 function by acting as adapters and facilitating coupling to effectors such as the inositol triphosphate receptor. However, although Homer proteins and their interaction with mGluRs have been the subject of intense study, direct measurements of Homer-induced changes in postsynaptic mGluReffector coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 48 publications
1
95
1
Order By: Relevance
“…We also found that the mGlu5-Homer interaction was reduced in wildtype animals after DHPG treatment (P , 0.05, unpaired t test). This is in accordance with sequestration of mGlu1/5 by Homer1a, which is translated locally in an activity-driven manner after DHPG treatment, thereby reducing the interaction of the long forms of Homer with mGlu1/5 (Kammermeier et al, 2000;Kammermeier and Worley, 2007). However, it should be noted that others have reported an increase in mGlu5-Homer interaction after DHPG treatment (Rong et al, 2003;Hu et al, 2012).…”
Section: Glud1 Regulates Mglu5 Signalingsupporting
confidence: 79%
“…We also found that the mGlu5-Homer interaction was reduced in wildtype animals after DHPG treatment (P , 0.05, unpaired t test). This is in accordance with sequestration of mGlu1/5 by Homer1a, which is translated locally in an activity-driven manner after DHPG treatment, thereby reducing the interaction of the long forms of Homer with mGlu1/5 (Kammermeier et al, 2000;Kammermeier and Worley, 2007). However, it should be noted that others have reported an increase in mGlu5-Homer interaction after DHPG treatment (Rong et al, 2003;Hu et al, 2012).…”
Section: Glud1 Regulates Mglu5 Signalingsupporting
confidence: 79%
“…The inducible short form of Homer1, Homer1a, is postulated to function as an intrinsic dominant negative by uncoupling between Homer-mediated target molecules (Kammermeier and Worley, 2007). In the present study, we demonstrated another mechanism for uncoupling of Homer target molecules by phosphorylation.…”
Section: Possible Physiological Roles Of Homer3 Phosphorylationmentioning
confidence: 54%
“…The long-form Homer proteins, Homer1b/c, Homer2, and Homer3, have the C-terminal coiledcoil region, which is responsible for their tetramer formation and enable to link target molecules at specific cellular regions, such as at excitatory postsynaptic sites (Hayashi et al, 2006). In contrast, Homer1a, which shows synaptic activity-dependent expression and fails to form tetramer attributable to lacking a coiled-coil region, is thought to function as a natural dominant negative to break clustering and/or linking target molecules (Brakeman et al, 1997;Kato et al, 1998;Kammermeier and Worley, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The continuous presence of Homer1a may therefore profoundly change neuronal signaling pathways that may in turn render the organism more vulnerable to chronic stress. In addition, it has previously been shown that interactions between NMDA and mGluR5 receptors are mediated by the PSD95/ Shank/Homer1 complex (Hayashi et al, 2009;Bertaso et al, 2010), and Homer1a was demonstrated to be a key modulator of mGluR5 coupling to effector targets that produce excitatory postsynaptic currents (Kammermeier and Worley, 2007). Given the increasing body of evidence showing that NMDA receptor targeting agents produce rapid-acting antidepressant effects (Krystal et al, 2013;Kavalali and Monteggia, 2012), a Homer1a-mediated overactivation of this signaling pathway may profoundly affect antidepressant treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%